PP57 Implementation of a novel intervention to care for elderly patients whofall: analysis of paramedics' views using Normalisation Process Theory. (2nd September 2014) - Porter, AM; Gaze, SA; Chatters, R; Koniotou, M; Anthony, R; Snooks, H
Abstract : Background: Many patients who fall and then call 999 are currently transferred to hospital even though there is no clinical need for them to go. The SAFER 2 study, in three UK ambulance services, evaluated a complex intervention to support paramedics safely to leave older patients at home with referral to a falls service, following a call to 999 for a fall. The intervention comprised a training programme, referral pathway, clinical support, clinical decision flowchart and referral feedback. A qualitative component within SAFER 2 aimed to understand whether the intervention had been successfully implemented into paramedics' practice. Normalisation Process Theory (NPT) examines the factors required for successful implementation of an intervention such as SAFER 2 into routine practice, through four components: coherence, cognitive participation, collective action and reflexive monitoring. We used NPT to frame an analysis of paramedics' views of implementation of SAFER 2. Methods: Four focus groups with paramedics were carried out pre-trial, and four post-trial. Two pre-trial interviews were carried out with paramedics who were not able to attend a focus group. Focus groups and interviews were recorded and transcribed in full. Transcripts were analysed using the framework approach, informed by NPT, by a team of four researchers. Results: 24 paramedics took part in pre-trial focus groups and interviews across the three sites, and 25 in post-trial focus groups. Pre-trial, there was not a clear or consistent understanding across sites of what the intervention was, and how it was distinct from similar interventions (coherence). Paramedics anticipated benefits of the new intervention, including improved patient care and job satisfaction, and thought that the referral pathway would be used widely (cognitive participation). During the trial, paramedics found that implementing the intervention led to increases of time on scene (collective action). The intervention was perceived as having some benefits to the ambulance service and patients in post-trial focus groups; paramedics from all three sites suggested improvements to the process which included simplification of the intervention (reflexive monitoring). Conclusion: Using NPT to frame the analysis of paramedic views on implementation of the SAFER 2 intervention highlighted issues with coherence and collective action that may have affected the trial. The novel intervention was seen as beneficial by paramedics during both pre- and post-trial interviews, although barriers to utilisation were identified.